The Need for Formal Surgical Global Health Programs and Improved Mission Trip Coordination - Sar Medoff (Ubiquity Press, 2016)
Background There is a dire need for more surgical services as part of improving global health. Conditions treatable with surgery account for 11% of the global burden of disease, with a disproportionate burden affecting low- and middle-income countries (LMICs). Less than 6% of the world’s operations are performed in LMICs, with relief organizations performing nearly 250,000 operations annually in LMICs in addition to each country’s domestic surgical capacity. Currently, surgical needs are not adequately met by the existing patchwork of federal and nongovernmental organizations’ surgical services and surgical mission trips. Improving coordination between mission trips may have synergistic benefits for maximizing the efficacy of the individual trips and improving the overall quality of care. Objectives To establish whether cooperation between surgical mission trips can lead to operational efficiency and to identify obstacles to cooperation. Methods In order to establish the veracity of cooperation translating into efficiency and to identify obstacles that prevent cooperation, a 50-question survey was created (see Supplement 1). The survey was sent to surgical program directors of the 147 major surgical programs in the United States and Canada with a follow-up telephone survey of 18 randomly selected programs. Findings The survey response rate was 14%. Although 90% of respondent programs mount at least 1 mission trip per year, only one-third confirmed the existence of global health or surgical global health programs at their institution (33%). There was significant interest in cooperating with programs at other institutions (80%). When asked why they do not communicate with humanitarian aid organizations doing similar work, 53% of respondents reported a “lack of knowledge of how to find similar organizations to mine doing similar work.” An additional 21% of respondents were “unaware that coordination is possible.” Conclusions A minority of respondent surgery programs host formal, organized surgical global health programs with a structured leadership based at academic medical centers. Although most institutions have individuals leading international humanitarian missions to LMICs, these leaders do not function in an integrated fashion with their departments, institutions, or other academic medical programs. The majority of respondents were interested in coordinating their surgical trips with other groups. Respondents suggested the creation of a central database that would allow trip organizers to share information about upcoming trips, site logistics, and personnel or supply needs.